INTELLECTUAL CAPITAL IN PUBLIC SECTOR - Budiarso, Novi Swandari (Universitas Sam Ratulangi, 2019)
This study explores the way in which intellectual capital characteristics contribute towards a competitive advantage to public sector firms, particularlyâ€“State Owned Enterprises (SOEs) in Indonesia. The purpose of this study was to investigate the relationship between the intellectual capital and performance of public sector firms.Â Another purpose was to find out the difference of SOEs and non SOEs listed on Indonesian Stock Exchange regarding the effect of intellectual capital on financial performance The motivation based on the opinion that public sector in Indonesia had a bad performance compares to private sector. In government context human capital include competence, level of knowledge and integrity. Structural capital consist of culture and system or bureaucracy. Customer capital pertaining services to public. The sample consist of 36 firms were listed in Indonesia Stock Exchange, 18 SOEs and 18 non SOEs. Data were drawn for three years, 2010-2012. It was an empirical study using multiple regression model and independent sample t test for the data analysis. The paper tests elements of VAICTM and financial companyâ€™s performance. The findings show that: as partial, the components of intellectual capital (VAICTM), physical capital have a significantly influences to firms performance, but human capital and structural capital have no significantly influences to firms performance.